A Smart Cloud-Based Energy Data Mining Agent Using Big Data Analysis Technology. Issue 3 (3rd July 2019) - Lin, Hsueh-Yuan; Yang, Sheng-Yuan
ABSTRACT: The aim of this paper was the development of a smart cloud-based energy data mining agent, OntoDMA, within the cloud environment Web service-based Information Agent System. Big Data analysis technology was used, embedded in a cloud-based active multi-agent system, to proactively provide fast and appropriate, real-time, domain information prediction. A case study was done to outline and explore the feasibility of the system architecture and the energy saving information system. A preliminary system presentation and experimental verification were prepared. The cache performance of the Solutions Pool was increased by 19.82% and the query workload of the Prediction Rules was reduced by 66.51%, a considerable decrease of the back-end servo system workload. Graphical Abstract: